CatStronauts Vol. 3, space station situation - Brockington, Drew (Brockington, Drew. CatStronauts, 2017)
"The CatStronauts--elite cat astronauts--are aboard the International Space Station to repair the faulty Hubba Bubba Telescope, but have to contend with communications interference and a near disaster that leaves them down a member"--